Laser-induced graphene (LIG)-based Au@CuO/V2CTx MXene non-enzymatic electrochemical sensors for the urine glucose test - Cui, Feiyun; Sun, Haiming; Yang, Xueqiong; Zhou, Hang; Wu, Yiqi; Li, Jing; Li, Hongxia; Liu, Jianlei; Zeng, Chijia; Qu, Bin; Zhang, Jufan; Zhou, Qin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
•Laser-induced graphene (LIG) electrodes were fabricated as one-off urine glucose test sensor strips.•Au@CuO nanocatalyst was synthesized to mimic the glucose oxidase and develop the urine glucose test sensor.•The effect of V2CTx MXene on the LIG-based non-enzymatic urine glucose test sensor was explored.•The developed sensor was demonstrated to achieve an ultrahigh sensitivity of 1.124 × 106 μA mM−1 cm−2. Glucose monitoring is of great significance for the health management of diabetic patients. Herein, non-enzymatic glucose sensors were developed by modifying Au@CuO or Au@CuO/V2CTx MXene nanocomposites (NCs) on the surface of disposable laser-induced graphene (LIG) electrode. The structures and morphologies were confirmed by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and elemental analysis. The electrochemical performances of NCs were investigated by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and chronoamperometry (CA). The results demonstrated that both Au@CuO/LIG and Au@CuO/V2CTx MXene/LIG have excellent electrocatalytic activity for glucose oxidation in an alkaline medium. However, it was found that Au@CuO/V2CTx MXene/LIG was easily oxidized. Hence, the combination of Au@CuO/LIG was preferred for glucose test. Under optimized conditions, the electrochemical sensor achieved a detection range of 0.005 to 5.0 mM with a sensitivity of 1.124 × 106 μA mM−1 cm−2. The response time was 1.5 s and the limit of detection (LOD) was as low as 1.8 μM. The sensor has good selectivity and stability (84.12 % activity retained after 6 weeks). Its affordable price, disposable usage and portable essence are suitable for clinical application. Our study presented a novel strategy to the field of non-enzymatic glucose sensing.